Seed with and without Partial Tegument Removal and Substrate Affect Germination of Castanea sativa - Ferreira, G. [UNESP]; Santos, G. R. [UNESP]; Costa, P. N. [UNESP]; Bueno, S. C. S.; Mischan, M. M.; Yamanishi, O. K. (Int Soc Horticultural Science, 2009)
Portuguese chestnut (Castanea sativa) is used for forest products, raw nuts and processed flour, paste, and candy. We studied the influence on germination efficiency of seed with and without partial tegument removal combined with different substrate composition (coconut fiber, pine compost and vermiculite) at São Paulo State University, Campus of Botucatu, São Paulo, Brazil. Randomized blocks were used in a factorial scheme 3x2 (three substrates x two seed types) consisting of six treatments with five replications (twelve seeds). Seeds were sowed in expanded polystyrene trays, with 72 cells, and maintained at 25 C under controlled environment. Rate, time elapsed and speed of seed germination was submitted to ANOVA and the average compared using Tukey's 5% test of probability and curves adjusted based on Gompertz regression. Coconut fiber or vermiculite associated with seed without partial tegument removal showed the highest germination rate, and coconut fiber with or without partial tegument removal displayed the fastest speed of seed germination.
Keywords: Portuguese chestnut; coconut fiber; vermiculite; pine compost